PERFORMANCE OF REINFORCED CONCRETE HOSPITAL BUILDING SUBJECTED TO EARTHQUAKE USING BASE-ISOLATION SYSTEM (Malaysian Journal of Civil Engineering, 2018)
The frequent occurrence of earthquake in the Bangladesh and up-gradation of seismic design code (BNBC-1993) has heightened the need for investigation of seismic performance of existing lifeline structure specially hospital building. The objective of this study is to evaluate seismic capacity and corresponding improvement of an existing hospital building (Ancillary Building) of Chittagong Medical College Hospital (CMCH). For this purpose, a three dimension (3-D) numerical model of Ancillary Building (AB) of CMCH was developed using SAP 2000 finite element program. A non-linear static analysis was performed to determine seismic capacity of the building model. The result indicates the seismic capacity of the hospital building is sufficient to mitigate the seismic demand according to BNBC-1993, whereas the seismic capacity is found insufficient as per revised BNBC. To reduce the seismic effect on AB, base-isolation devices have been designed and were used as link element to the numerical model. The application of base-isolation devices as a retrofitting strategy makes the considered hospital building safer for seismic excitation suggested in revised BNBC.